Effect of Addition of Polyurea as an Aggregate in Mortars: Analysis of Microstructure and Strength (2022)
The addition of polymers in construction is a new tendency and an important step toward the production of structures with better functional properties. This work investigates the addition of polyurea (PU) as a polymeric material in mortars. Polymer mortars were manufactured with the addition of polyurea retained in different sieves (T50 and T100) and different concentrations (2% and 5%). The characterization of the, polyurea (PU)control mortar (PU0%) and manufactured polyurea mortars (PU2%T50, PU5%T50, PU2%T100, and PU5%T100) was conducted by means of morphological analysis, SEM, XRF, TGA, and a compressive strength test of hydraulic mortars. The results show that mortars with polyurea retained in sieve 100 with a particle size of 150 µm exhibit better thermal behavior and a greater resistance to compression with a concentration of 5% polyurea with respect to the other samples. The present work reveals that polyurea retained in sieve 100 can be considered as a polymeric additive for mortars, indicating that it could be a candidate for applications such as construction. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.